A Model Scale Real-Time Sorting and Monitoring Production Line System with The Integration of Labview Gui - Suhaimi, Muhamad Syafiq; JALALUDIN, DR NOR ANIJA (Progress in Engineering Application and Technology, 2023)
The main purpose of this project is to provide exposure to the automated process of simulation and theory to compile products among students who are studying in the engineering field. The main research objectives is to design a Model Scale Real time Autonomous Process Control for Production Line System with the integration of LabVIEW GUI and the scopes of study is will place Lego as the product that moving material on conveyor line. Materials will use camera, servo, dc motor, Arduino, conveyor, IR sensor and a type C metal as the main mechanism, and Labview platform will utilized to obtain the image to analyze and an Arduino hardware to control the output actuator. In the finding output result, performance of image capturing affecting effectiveness sorted product. Emphasizing automated system or process flow can achieve high product quality output beside low time consume and low cost invest in a manufacturing business.